Monitoring finansowy w zarządzaniu organizacjami charytatywnymi na przykładzie stacji opieki - Dyczkowski, Tomasz (Financial Monitoring in Management of Charities the Example of a Home Care Centre, 2006)
The paper presents an example of a monitoring system based on solutions developed by German home care centres. The first part of the article defines five stages of implementation of a monitoring system in nonprofit organisations. An analysis of information requirements of home care centres -with emphasis on database and management reporting - is carried out subsequently. Eventually, the author highlights objectives of observation of selected key ratios and discusses necessity of adjustments in existing solutions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 56-67